Underuse of reperfusiontherapy in STEMI with cardiogenic shock. Results of the EORP ACVC EAPCI STEMI registry of the ESC. (14th October 2021) - Zeymer, U; Ludman, P; Danchin, N; Kala, P; Gale, C; Maggioni, A; Weidinger, F
Abstract: Aims: To determine the current state of the use of reperfusion and adjunctive therapies and in-hospital outcomes in ESC member and affiliated countries for patients with ST segment elevation myocardial infarction (STEMI) complicated by cardiogenic shock (CS). Methods and results: ESC EORP prospective international cohort study of admissions with STEMI within 24 hours of symptom onset (196 centers; 26 ESC member and 3 affiliated countries). Of 11462 patients enrolled, 448 (3.9%) had CS. Patients without compared to patients with CS, more frequently received primary PCI (72.5% versus 65.2%) and fibrinolysis (19.0 versus 15.9%) and less frequently had no reperfusion therapy (8.5% versus 19.0%). Mechanical support devices (IABP 11.2%, ECMO 0.7%, other 1.1%) were used infrequently in CS. BARC 2–5 bleeding complications (10.1% versus 3.0%, p<0.01) and stroke (4.2% versus 0.9%, p<0.01) occurred more frequently in patients with CS. In-hospital mortality was ten-fold higher (35.5% versus 3.1%) in patients with CS. Mortality in patients with CS in the groups with PCI, fibrinolysis and no reperfusion therapy were 27.4%, 36.6% and 62.4%, respectively. Conclusions: In this multi-national registry patients with STEMI complicated by CS less frequently receive reperfusion therapy than patients with STEMI without CS. Early mortality in patients with CS not treated with primary PCI is very high. Therefore strategies to improve clinical outcome in STEMI with CS are needed. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): ESC EORP